Green human resource management research in emergence: A review and future directions - Ren, Shuang; Tang, Guiyao; E. Jackson, Susan (Asia Pacific journal of management, 2018)
The growing awareness of and regulations related to environmental sustainability have invoked the concept of green human resource management (GHRM) in the search for effective environmental management (EM) within organizations. GHRM research raises new, increasingly salient questions not yet studied in the broader human resource management (HRM) literature. Despite an expansion in the research linking GHRM with various aspects of EM and overall environmental performance, GHRM’s theoretical foundations, measurement, and the factors that give rise to GHRM (including when and how it influences outcomes) are still under-specified. This paper, seeking to better understand research opportunities and advance theoretical and empirical development, evaluates the emergent academic field of GHRM with a narrative review. This review highlights an urgent need for refined conceptualization and measurement of GHRM and develops an integrated model of the antecedents, consequences and contingencies related to GHRM. Going beyond a function-based perspective that focuses on specific HRM practices and building on advances in the strategic HRM literature, we discuss possible multi-level applications, the importance of employee perceptions and experiences related to GHRM, contextual and cultural implications, and alternative theoretical approaches. The detailed and focused review provides a roadmap to stimulate the development of the GHRM field for scholars and practicing managers.